SERIES: eHealth in primary care. Part 4: Addressing the challenges of implementation. (16th December 2020) - Versluis, Anke; van Luenen, Sanne; Meijer, Eline; Honkoop, Persijn J.; Pinnock, Hilary; Mohr, David C.; Neves, Ana Luisa; Chavannes, Niels H.; van der Kleij, Rianne M. J. J.
Abstract: Background: The implementation of eHealth applications in primary care remains challenging. Enhancing knowledge and awareness of implementation determinants is critical to build evidence-based implementation strategies and optimise uptake and sustainability. Objectives: We consider how evidence-based implementation strategies can be built to support eHealth implementation. Discussion: What implementation strategies to consider depends on (potential) barriers and facilitators to eHealth implementation in a given situation. Therefore, we first discuss key barriers and facilitators following the five domains of the Consolidated Framework for Implementation Research (CFIR). Cost is identified as a critical barrier to eHealth implementation. Privacy, security problems, and a lack of recognised standards for eHealth applications also hinder implementation. Engagement of key stakeholders in the implementation process, planning the implementation of the intervention, and the availability of training and support are important facilitators. To support care professionals and researchers, we provide a stepwise approach to develop and apply evidence-based implementation strategies for eHealth in primary care. It includes the following steps: (1) specify the eHealth application, (2) define problem, (3) specify desired implementation behaviour, and (4) choose and (5) evaluate the implementation strategy. To improve the fit of the implementation strategy with the setting, the stepwise approach considers the phase of the implementation process and the specific context. Conclusion: Applying an approach, as provided here, may help to improve the implementation of eHealth applications in primary care.